The Nightmare of Indifference: Shakespeare’ s Sonnet 121 and the War in Former Yugoslavia - Lupić, Ivan (Array, 2008)
The chapter addresses the attractions of reading Shakespeare's sonnets contextually. It discusses the ways in which different con-texts contribute to the constitution of the meanings of these poems by conditioning readers' expectations in various ways. In the case of the sonnets, con-texts primarily denote those within which a particular sonnet is embedded in the 1609 quarto order, but also those texts in relation to which a particular sonnet is made to function at a certain moment of its publication history. This "historically situated embodiment" of a Shakespeare sonnet becomes particularly fascinating when one is confronted with a translation, the contexts of which are foreign in more senses than one and serve to release meanings not immediately noticeable or not accorded a prominent position in the overall semantic design of the poem in question. The focus of the discussion is the translation of Shakespeare’ s sonnet 121, published in one of the most popular Croatian daily newspapers in 1991. This was the year in which the war in Croatia could be said to have already begun. Prompted by the immediate textual environment of the newspaper in which the sonnet was published as well as by the accompanying translator's note, the discussion will be moving from religious contexts (including the shrine of Holy Trinity Church in Stratford-upon-Avon, England) to the contexts of the Yugoslav war and textual burial of 1991.